INDUCED BREEDING GOLDEN BLACK MOLLY USED DIFFERENT SALINITY - Safitri, Wilda; Diniarti , Nanda; Dwi Hari Setyono, Bagus (Jurnal Media Akuakultur Indonesia, 2022)
Poecilia sp. is one type of ornamental fish that has distinctive characteristics because molly fish are freshwater ornamental fish that are able to live and breed in saline (brackish water) environments. Induction of molly fish spawning can be done with salinity treatment on the spawning media because the endocrine system in molly fish which plays a role in regulating body balance against changes in environmental conditions, especially changes in salinity will become more active so that it affects metabolism and reproduction (Taufik & Kusrini, 2006). The purpose of this study was to analyze differences in salinity as a spawning stimulant in molly fish. the method used in this study: P1. Salinity 10 ppt, P2. Salinity 15 ppt, P3. salinity 20 ppt, P4. Salinity 25 ppt, P5. 30 ppt with three replications. Parameters observed were Gonad Maturity Level (TKG), Gonad Maturity Index (IKG), survival rate (SR), and gestation period. The reared fish showed good gonad maturity so that spawning occurred. The results of this study, the highest gonadal maturity level was found at P1 salinity 10 ppt and P2 salinity 15 ppt the best, namely TKG V compared to P3, P4, and P5 namely TKG IV. The best gonadal maturity index was treatment P1 which was 14.28±2.0c followed by P2 11.71±2.0bc, P3 10.74±0.76abc P5 8.01±2.34ab and P4 7.27±2, 84a. The fastest gestation period was in P1 and P2, namely 44 days and 23 days. The highest survival rate occurred in P1 and P2, which was 100%. The highest absolute weight average was found in P1 which was 8.01±0.82c P2 6.33±0.5bc. The conclusion of this study, different salinity has a significant effect on the gonadal maturity index and absolute weight of golden black molly fish.